A correlation between gastrointestinal dysfunction and cirrhosis severity. Issue 37 (September 2018) - Wang, Ping; Zhang, Ying-Jian; Li, Yi-Ran; Liu, Xiao-Min; Lv, Shu-Yan; Xia, Xiao-Yan
Abstract : Abstract: This study aims to investigate the relationship between gastrointestinal dysfunction (GD) and cirrhosis severity in cirrhotic patients, to provide evidences for the prevention and treatment of GD in cirrhotic patients. A total of 95 cirrhotic inpatients and outpatients, who were treated in the Department of Gastroenterology of Xinqu Hospital of the First Affiliated Hospital of Henan University of Science and Technology, were enrolled in the present study, and assigned as the experimental group (cirrhosis group). According to Child–Pugh classification, these patients were divided into 3 groups: group A ( n = 45), group B ( n = 23), and group C ( n = 27). Forty healthy adults who received health check-ups during the same period served as the control group. The gastrointestinal (GI) symptoms of cirrhotic patients were scored, and the fasting serum gastrin (GAS), motilin (MTL), and vasoactive intestinal peptide (VIP) levels were measured in all subjects. The potential correlations of GI symptom scores of patients in these cirrhosis groups with GI hormone levels and cirrhosis severity were analyzed. In cirrhotic patients, the GI symptom scores significantly increased. Furthermore, the symptom scores gradually increased along with the aggravation of liver damage. Moreover, serum GAS and VIP levels were significantly higher in the cirrhosis groups than in the control group, whereas MTL levels were significantly lower. These changes were significantly correlated with cirrhosis severity. The linear correlation analysis revealed that the GI symptom score was positively correlated with GAS and VIP levels, and negatively correlated with MTL level. In addition, the linear correlation analysis revealed that GI symptom score and GAS and VIP levels were positively correlated with cirrhosis severity, whereas MTL level was negatively correlated with cirrhosis severity. Cirrhotic patients have more obvious GI symptoms and higher GI hormone levels, which are closely correlated with the progression of liver cirrhosis and the degree of liver function damage.